PENANGANAN KEKERASAN TERHADAP ANAK BERBASIS MASYARAKAT DI INDONESIA - Ika Harni Lestyoningsih (Lambung Mangkurat, 2019)
Cases of child abuse are an international issue with cases starting to increase. Also happens in Indonesia, but the condition of children is still marginalizing. This research method uses literature review. Articles are collected using search engines such as Science direct and EBSCO. The criteria for the articles used are those published in 2014-2018. This research is to collect and analyze articles relating to the handling of community-based child abuse. Based on the results, that the situation of violence against children is an issue behind the still high mortality and morbidity of children. This condition is aggravated by other factors that come from within the family and external factors outside the family environment. Handling of victims of violence against children in Indonesia has been carried out, both by various institutions, both government institutions, and non-governmental organizations. However, cross-sectoral coordination is still a problem. The conclusion is the handling of child victims and perpetrators of comprehensive violence through comprehensive treatment and involving various competent parties.